Mycophenolate mofetil for autoimmune cytopenias in children: high rates of response in inborn errors of immunity - Berrueco, Rubén; González-Forster, Elisa; Deya-Martinez, Angela; Solsona, María; García-García, Ana; Calzada-Hernández, Joan; Yiyi, Luo; Vlagea, Alexandru; Ruiz-Llobet, Anna; Alsina, Laia (Frontiers in Pediatrics, 2023)
Second-line treatments in autoimmune cytopenias (AC) are not well-defined in children. Mycophenolate mofetil (MMF) is an immunosuppressant agent that has been demonstrated to be safe and effective in this setting. A retrospective observational study was performed in 18 children with prolonged AC who received MMF, in order to describe clinical and biological markers of response. Overall response rate to MMF at 20-30 mg/kg per day was 73.3%. All patients with Evans syndrome (n=9) achieved complete response. Among patients with monolineage AC (n=9), those with an underlying IEI tended to respond better to MMF. No biological markers related to treatment response were found. Rather, lymphocyte subpopulations proved useful for patient selection as a marker suggestive of IEI along with immunoglobulin level determination.